Pelatihan Penerapan Pembayaran QRIS pada UMKM untuk Meningkatkan Efisiensi Transaksi - Teyensi, Teyensi; Nistiani, Anela; Febrianti, Ledya; Harpepen, Andi (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
The advancement of digital technology encourages Micro, Small, and Medium Enterprises (MSMEs) to adopt more efficient cashless payment systems. QRIS (Quick Response Code Indonesian Standard) is one of the innovative solutions implemented to enhance transaction efficiency in the MSME sector. This study aims to analyze the implementation of QRIS at the Geprek Cila MSME and its impact on financial transaction efficiency. The activities were conducted using a Participatory Action Research (PAR) approach, through field observations, training, and technical assistance. The results show that the use of QRIS accelerates the payment process, minimizes the risk of error and cash loss, and improves the accuracy of financial records. Furthermore, the implementation of QRIS supports financial inclusion and enhances consumer trust. This study recommends continuous assistance and the enhancement of digital literacy among MSME actors to support equitable and sustainable digital transformation.